Effect of Hemoadsorption for Cytokine Removal in Pneumococcal and Meningococcal Sepsis. (19th June 2018) - Leonardis, Francesca; De Angelis, Viviana; Frisardi, Francesca; Pietrafitta, Chiara; Riva, Ivano; Valetti, Tino Martino; Broletti, Valentina; Marchesi, Gianmariano; Menato, Lorenza; Nani, Roberto; Marson, Franco; Fabbris, Mirca; et al.
Abstract : Bacterial meningitis and septicemia are invasive bacterial diseases, representing a significant cause of morbidity and mortality worldwide. Both conditions are characterized by an impressive inflammatory response, resulting rapidly in cerebral edema, infarction, hydrocephalus, and septic shock with multiple organ failure. Despite advances in critical care, outcome and prognosis remain critical. Available adjunctive treatments to control the inflammatory response have shown encouraging results in the evolution of patients with sepsis and systemic inflammation, but meningococcal or pneumococcal infection has not been investigated. We herein report five patients with similar critical pathological conditions, characterized by pneumococcal or meningococcal sepsis and treated with hemoadsorption for cytokine removal. All patients showed a progressive stabilization in hemodynamics along with a rapid and marked reduction of catecholamine dosages, a stabilization in metabolic disorders, and less-than-expected loss of extremities. Therapy proved to be safe and well tolerated. From this first experience, extracorporeal cytokine removal seems to be a valid and safe therapy in the management of meningococcal and pneumococcal diseases and may contribute to the patient stabilization and prevention of severe sequelae. Further studies are required to confirm efficacy in a larger context.